DETERMINASI PENYESUAIAN DIRI YANG DIPENGARUHI SELF EFFICACY DAN DUKUNGAN TEMAN BERIMPLIKASI PADA PRESTASI AKADEMIK - Dewi Herliyanti; Heti Suherti; Edi Fitriana Afriza (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Various problems faced by students in the early semester can be overcome if balanced with comprehensive adjustments so the goals of learning outcomes related to academic achievement will be good. This research focuses on student academic achievement in the early semester which is still not optimal because they have to adapt to their environment. Individual personal beliefs and the support of friends really help the process of adaptation to student self adjustment. The research method used was a quantitative type of survey. 200 early semester students form outside the West Java area at Siliwangi University were the sample in this study and the sampling technique used nonprobablity sampling, namely saturated samples. Data collection techniques using quistionnaries and data analysis techniques using path analysis. The results of the study show that based on self efficacy test and peer support, each has direct effect on self adjustment. Then another result in obtained that peer support does not have a direct effect on academic achievement while self efficacy and self adjustment each have a direct effect on academic achievement. Based on the path analysis test shows that self efficacy and peer support each have an indirect effect on academic achievement through self adjustment as an intervening variable.